Проблемы правового регулирования лесных правоотношений в Республике Казахстан (Journal of actual problems of jurisprudence, 2019)
In this article reviews some of the confusion of the current Forest Code of the Republic of Kazakhstan, and also provides somesuggestions for its improvement.